Self-representation of LGBT individuals through nomination and predication strategies. - Jiin Yih, Yeo; Ting, Su Hie; Collin, Jerome (2022)
Identifying as LGBT is not as simple as it appears in Malaysia where non-normative genders and sexualities are susceptible to social-legal criticism (Teh, 2008). In Malaysia, same-sex unions are not recognised and those commit same-sex sexual activity will be fined, jailed and canned (Hamidah, 2004). Although LGBT is still unacceptable in Malaysia, younger generation, particularly young men are more open in disclosing their diverse sexual orientations through social media in this digital age (Jerome, 2008). There are plenty of LGBT individuals who are living the homosexual lifestyle (Zainon et al, 2018) and they are experiencing the complexity and multidimensional nature of sexual identity development. Therefore, there is a need for a new understanding of how LGBTs in Malaysia define their identities in relation to sexuality. This study aimed to examine how nomination and predication strategies are employed by LGBT individuals to represent themselves. This study involved seven LGBT individuals from different ethnic and religious backgrounds in Malaysia. The participants were in their twenties to forties. The participants self-identified as panromantic – asexual, gay, queer, bisexual and non-binary. Snowball sampling technique was employed to identify LGBT participants. The narrative data were gathered through semi-structured interviews. The interviews were transcribed verbatim. The seven interviews totalled 240 minutes and the transcript was 33,162 words. The interview transcripts were analysed using Reisigl and Wodak’s (2017) discourse-historical approach. The discourse-historical approach includes five discursive strategies together with the questions to approach discursive features. They are nomination (How are persons, objects, phenomena/events, processes, and actions were named and referred to linguistically?), predication (What characteristics, qualities, and features were attributed to social factors, objects, phenomena/ events and processes?), argumentation (What arguments were employed in the discourse in questions?), perspectivisation (From what perspective are these nominations, attributions, and arguments expressed?) and mitigation/intensification (Are the respective utterances articulated overtly? Are they intensified or mitigated?) Specifically, the analysis focused on nomination and predication strategies. The analysis of nomination strategy is aimed at seeing how LGBTs representing themselves while the analysis of predication is used to see how LGBTs discursively described themselves through some characteristics attributed to them. The findings of the study reveal that most of the LGBTs used LGBT-linked referents to disclose their identities, namely, “lesbian”, “gay (couple/people)”, “bisexual”, “trans-gender/people/woman”, “queer”, “third gender”, “intersex people”, “non-straight friends”, “pondan”, “maknyah”, “LGBT”, and “LGBT community/people”. In the Malaysian context, “pondan” refers “Malay men who are effeminate or feminine in their appearances, mannerisms, and/or behaviours” while “maknyah” describes “Malay male-to-female transsexuals” (Jerome, 2013, p.171). One gay participant expressed his frustration when inaccurate terms such as “pondan” or “maknyah” were used to refer to them. Another Malay participant expressed that she felt comfortable with the term “queer” to represent her identity and to convey a sense of community. These indicate that the participants were grappling with issues of how they are referred to. The self-representation of LGBT participants was either positive or neutral, in contrast to the negative other-presentation based on the participants’ views of or on Us (in-group) and Them (out-group). Most LGBTs used terms such as “family”, especially “parents”, “older generation”, the government and authorities to represent groups of people who hate, despise, and reject them. Fathers and uncles are more likely to reject them compared to mothers, aunts and sisters. Positive other-presentation is linked to peers (“roommate”, “best friend”) and female, siblings, and younger members of the family. As for other people in society, activists and volunteers connote positive nominations but colleagues, teachers, neighbours, politicians, Muslims and Malays connote negative nominations. Analysis of the positive predicate qualifications show that a majority of the LGBTs evaluated and qualified themselves as (1) normal, (2) comfortable, (3) accept self, (4) liberated and (5) hopeful. These adjectives are used to construct the LGBT individuals as living a normal life after they have come out. They feel liberated to disclose their true identity. The LGBT participants are comfortable with their own way of living and they have accepted their sexuality as a part of their self. They are sure of their own identity and have also got used to living with social stigma. At the end of the interviews, many expressed hopes to be treated kindly as a human being and will be protected by law. Their hopes imply that there is the possibility of a better future and thus can help make their present situation more endurable. However, some LGBTs described themselves negatively as (1) cause for societal ills, (2) afraid of coming out, (3) seen as unreligious, (4) being misunderstood, (5) being discriminated and (6) overwhelming negative emotions. Based on the participant’s disclosure, LGBTs are often associated with HIV, drug abuse, misuse of the Grindr Application for finding sex partners, unreligious behaviour, and mental illness. The participants qualified the negative state caused by “they” or the “other group” in negative terms revolving around anger, depression, disappointment and sadness. The findings reveal that LGBT participants employed nomination and predication strategies in representing themselves and revealing their stance towards the mainstream ideologies. In contrary to Shamsudin and Ghazali’s (2011) study, LGBT individuals in this study did not conform to the cultural norm and values where LGBT is not normal. In fact, most of the LGBT participants, who did not go through struggles of coming out, expressed their joy as part of LGBT community. References Hamidah, A. (2004). United Nation ill-advised on homosexual laws. http://www.glapn.org/sodomylaws/world/malaysia/mynews035.htm Teh, Y. K. (2008). Politics and Islam: factors determining the identity and status of male-to female transsexuals in Malaysia. In F. Martin, P.A. Jackson, M. McLelland & A. Yue (Eds.), AsiaPacifiQueer: rethinking genders and sexualities (pp. 85–98). University of Illinois Press. Zainon, S., Zarihan, S., Mohd Faizal, M. A., & Syarifah Shahirah, S. S. (2018). The discursive strategies used by young homosexual males in the construction of their identity. Advances in Intelligent Systems and Computing, 739, 712–720. Reisigl, M., & Wodak, R. (2017). The Discourse-Historical Approach (DHA). In J. Flowerdew & J. E. Richardson (Ed.). The Routledge handbook of critical discourse studies (pp.87-119 ). Routledge. Jerome, C. (2008). Sexual identities of the Malay male in Karim Raslan’s go east and neighbours. GEMA Online® Journal of Language Studies, 8(1), 35–46. Shamsudin, Z., & Ghazali, K. (2011). A discursive construction of homosexual males in a Muslim-dominant community, Multilingua, 30(3-4), 279-304.